Active Intuition: The Patterned Spontaneity of Decision-Making - Williams, Lawrence Hamilton (Frontiers in Sociology, 2018)
Sociologists have been split between explaining individual thought and action in terms of factors internal and external to any given individual. In this paper, I argue that while these two explanations may often be complementary, they do not amount to a complete account of how people actually think or act. Using secondary interviews conducted with individuals tasked to think about death and dying, I demonstrate how individuals actively intuit their surroundings using complex mixtures of both the environment that they have internalized as well as the environment(s) that they are currently in. Using the terms cognitive field and active intuition to describe this process of meaning-making, I assert that existing sociological explanations could benefit from taking into consideration both the emergent nature of individuals’ perception of the worlds they live in as well as the iterative nature of the interview process.